2017
DOI: 10.1021/acs.orglett.7b03287
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of a Sizeable Nonclassical CH···G Hydrogen Bond in Cyclohexane Derivatives: Stabilization of an Axial Cyano Group

Abstract: Base-catalyzed equilibration of anancomeric cyanocyclohexanes demonstrates that replacement of cis-3,5-dimethyl holding groups with electron-withdrawing CF groups dramatically increases the proportion of the axial cyano isomer present at equilibrium. The CF groups exert an effect on the conformational energy of the cyano group worth about 0.6 kcal/mol. A nonclassical hydrogen bond between the axial CN group and the syn-axial hydrogens is a major contributor to the axial stability of the group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…We recently presented evidence for an attractive, nonbonded Coulombic interaction of the type CH•••G in a simple cyclohexane derivative that serves to stabilize an axial CN group. 17 As illustrated in Figure 2, replacement of cis-3,5dimethyl holding groups in anancomeric models with electronwithdrawing CF 3 groups dramatically increases the proportion of the axial cyano isomer present at equilibrium in cyclohexane solvent. The CF 3 groups render both the C(3,5) carbons as well as the attached syn-axial hydrogens more positive vis-a-vis the 3,5-dimethyl cyclohexane.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently presented evidence for an attractive, nonbonded Coulombic interaction of the type CH•••G in a simple cyclohexane derivative that serves to stabilize an axial CN group. 17 As illustrated in Figure 2, replacement of cis-3,5dimethyl holding groups in anancomeric models with electronwithdrawing CF 3 groups dramatically increases the proportion of the axial cyano isomer present at equilibrium in cyclohexane solvent. The CF 3 groups render both the C(3,5) carbons as well as the attached syn-axial hydrogens more positive vis-a-vis the 3,5-dimethyl cyclohexane.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, it is known from experimental studies that the hydrogen of C−H bonds in alkanes has a small positive charge 18 and a more modest CH•••CN hydrogen bond may also be involved in the di-CH 3 system. 17 In an effort to explore the extent to which Coulombic interactions of this kind contribute to an anomeric effect in heterocyclic systems, we have investigated the axial−equatorial energy difference in 1,3-dioxanes bearing 2-OCH 3 or 2-CN substituents. Conformational equilibria of this sort are investigated most conveniently by equilibration of configurationally isomeric models for the conformational isomers and, as Eliel has demonstrated, 19 a cis-4,6-dimethyl-1,3-dioxane is a good surrogate for the unbiased system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The enynamide might be stabilized by the regulation of its molecular conformation and increased the barrier to rotation of the C–C bond a , so that the nucleophilic attack of the oxygen atom was unfavored. Based on our previous research about the N -quinolone amide, this hypothesis might be achieved with N -quinolone enynamides as the substrate due to the interaction of its intramolecular H-bonds (Scheme , eq 3) . This assumption was indeed supported by the H-bonds (N–H···N and C–H···O) and approximately plane conformation of enyamide 1m observed in the X-ray crystal structure (see SI), in which the oxygen and alkynyl group were on the opposite side of the C–C single bond a .…”
mentioning
confidence: 77%
“…The increased charge could also be seen in calculations. 12 It has also been found that hydrogens are quite sensitive to electronic effects at the atom to which they have been attached. With only a small nuclear charge, it is readily possible to shift some charge either to or from a hydrogen atom.…”
Section: Hydrogen Atom Problemmentioning
confidence: 96%
“…This led to an increased Coulombic attraction with the axial F that could be observed via equilibrium constant measurements. The increased charge could also be seen in calculations …”
Section: Hydrogen Atom Problemmentioning
confidence: 99%